Awareness of breast cancer among adolescent girls in Lombok Tengah - Nur Wahida; Saimi Saimi (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Knowledge of BSE among adolescents is very high. Through breast self-examination, early changes can be detected, health awareness can be increased, and breast cancer prevention can be contributed. Breast cancer is one of the most common types of cancer in women and is a malignant tumor that grows in breast tissue. Early detection is needed to prevent breast cancer in adolescents. State Senior High School 1 Batukliang is one of the Senior High Schools in Batukliang District, Central Lombok Regency that has not received information about breast cancer. Purpose: To determine the relationship between the level of knowledge of female adolescents in grade XII of State Senior High School 1 Batukliang and efforts to detect breast cancer early. Method: This is an analytical observational study using a cross-sectional research design that only takes data at one time, which was conducted from July to December 2023. The population in this study were all female adolescents in grade XII of State Senior High School 1 Batukliang totaling 68 people. Data analysis was carried out using univariate analysis and bivariate analysis using the Chi square test and Spearman test. Results: The majority of respondents were at a high level of knowledge of 27 respondents (46.6%), sufficient knowledge of 25 respondents (43.2%), and the lowest knowledge of less than 6 respondents (10.3%). In addition, most female students made early detection efforts, namely 36 respondents (62.1%) and those who did not make early detection efforts were 22 respondents (37.9%). Based on the Spearman test, there was a statistically significant relationship between BSE knowledge and the attitudes of young women (ρ value = ​​0.00 <0.05). Conclusion: There is a relationship between the level of respondent knowledge and early detection efforts of breast cancer in Central Lombok Regency in 2023, with the results of the chi square test obtained a value of ρ = ​​0.000 <0.05.